ANALYSIS OF MINERAL CONTENT IN ZAM-ZAM WATER CIRCULATION IN PADANGSIDIMPUAN CITY - Harahap, Fatma Suryani; Pohan, Heni Mulyani; Siregar, Rabiyatul Adawiyah; Elisa, Elisa; Lubis, Jalilah Azizah; Latifah, Nur (Universitas Medan Area, 2024)
This research was motivated by the existence of Zam-zam water trade in Padangsidimpuan City, while the Saudi Arabian government prohibited the export of Zam-zam water. This causes people to suspect that the quality of Zam-zam water circulating in the market is not the same as the Zam-zam water found in Mecca. Therefore, research needs to be carried out to answer these concerns. This research aims to analyze the mineral content of labeled packaged Zam-zam water circulating in Padangsidimpuan City compared with Zam-zam water brought from Mecca City. The mineral concentrations tested were sodium and chloride. This research uses laboratory experimental methods, including quantitative analysis. According to the type of research, the data analysis technique used is to compare the concentration of each mineral in the water labeled Zam-zam with the mineral concentration in the Zam-zam water used as a control. The research results showed that Zam-zam water obtained from Mecca City contained 42.4 mg/L chloride, 2.06 mg/L sodium, while the labeled Zam-zam water circulating in Padangsidimpuan, namely sample 1, contained 160.7 mg/L chloride. sodium 2.06 mg/L in sample 2 contains 50.5 mg/L chloride, sodium 2.17 mg/L. The three Zam-Zam samples circulating in Padangsidimpuan that have been tested show that the quality of Zam-Zam water is suitable for consumption based on determining a good water quality test, namely at the suitability threshold.